PENGARUH POP-UP BOOK PADA MATERI KEBERAGAMAN BUDAYA INDONESIA UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS V SD INPRES SIAPUTIH - Febri Kamelane; Leonid Ritiauw; Fadhilah Hukmiah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Students' learning motivation in Indonesian Cultural Diversity material in elementary schools remains low due to conventional textbooks lacking visual stimuli. This quantitative study aims to analyze the effect of pop-up book media on the learning motivation of fifth-grade students at SD Inpres Siaputih regarding Indonesian Cultural Diversity. The study employed a pre-experimental one group pretest-posttest design involving a sample of 12 students. Data were collected via structured questionnaires and analyzed using paired sample t-test and N-gain tests. The paired sample t-test yielded a significance value of 0.000 (p<0.05), indicating a significant difference in learning motivation before and after treatment. The N-gain calculation showed a mean score of 0.65 or 78.91%, categorized as moderate improvement. The three-dimensional visual features of the pop-up book media provided concrete stimuli that strengthened students' attention and satisfaction in learning. In conclusion, the application of pop-up book media contributes positively to enhancing elementary students' learning motivation in cultural diversity material. ABSTRAK Motivasi belajar siswa pada materi Keberagaman Budaya Indonesia di sekolah dasar tergolong rendah akibat penggunaan buku teks konvensional yang minim stimulus visual. Penelitian kuantitatif asosiatif ini bertujuan menganalisis pengaruh media pop-up book terhadap motivasi belajar siswa kelas V SD Inpres Siaputih pada materi Keberagaman Budaya Indonesia. Penelitian menggunakan desain pre-experimental one group pretest-posttest design dengan sampel 12 siswa. Data dikumpulkan melalui angket terstruktur dan dianalisis menggunakan uji paired sample t-test serta N-gain. Hasil analisis paired sample t-test menunjukkan nilai signifikansi sebesar 0,000 (p<0,05), yang mengindikasikan adanya perbedaan motivasi belajar yang signifikan sebelum dan sesudah perlakuan. Perhitungan N-gain menghasilkan rerata sebesar 0,65 atau 78,91% yang masuk dalam kualifikasi peningkatan sedang. Karakteristik visual tiga dimensi dari media pop-up book mampu memberikan stimulus konkret yang memperkuat aspek perhatian dan kepuasan siswa dalam belajar. Kesimpulannya, penggunaan media pop-up book berkontribusi positif dalam meningkatkan motivasi belajar siswa sekolah dasar pada materi keberagaman budaya.